IMPRESSION DIMENSIONAL CHANGE OF POLYVINYL SILOXANE LIGHT AND MEDIUM BODY MATERIAL BY USING PERFORATED TRAY : PERUBAHAN DIMENSI CETAKAN BAHAN CETAK POLYVINYL SILOXANE LIGHT DAN MEDIUM BODY DENGAN MENGGUNAKAN SENDOK CETAK BERLUBANG - Sumadhi Sastrodihardjo; Dahliana Purba (Dentika: Dental Journal, 2013)
Generally impression materials including elastomer impression materials show dimensional changes after impression taking. There are many investigations that show these dimensional changes with several causal factor possibilities proposed by the authors. The actual causal factor has not been elucidated yet. The aim of this study was to find out the behaviour and dimensional changes occured in two types of elastomeric impression consistency materials by using perforated tray. Light and medium body types of polyvinyl siloxane impression materials were used in this study. Impression consistency materials were tested with the method noted at the ANSI/ ADA specification no.19-2000. Design of study post-test only. Impression was taken by using perforated metal tray on frustum conical metal master die (n= 10 impressions/material). The dimensions of samples were measured by using digital calliper (Mitutoyo, Japan) at base, top area and height. The dimensional changes were calculated from master and stone die measurement. The results showed that there were dimensional changes occured in all of observed areas. Light body type showed dimensional changes at base, top area and height as many as (+) 0.032 ± 0.016 mm, (-) 0.136 ± 0.045 mm and (+) 0.112 ± 0.022 mm, respectively. Medium body type showed dimensional changes at base, top area and height as many as (+) 0.009 ± 0.013 mm, (-) 0.090 ± 0.016 mm and (+) 0.085 ± 0.010mm, respectively. In conclusion, there were significant differences between light and medium body types of polyvinyl siloxane impression materials caused the quantity of dimensional changes on impression (p< 0.05). Stress releasing passes through the holes on perforated tray may take a possible role to cause different direction of dimensional changes on impression.